Quartz-enhanced photoacoustic spectroscopy for SF6 gas matrix based on a T-shaped quartz tuning fork - Sun, Bo; Li, Yue; Gao, Zhijian; Zhang, Mingjiang (Frontiers in Physics, 2025)
This paper presents the design and fabrication of a T-shaped quartz tuning fork (QTF) for quartz-enhanced photoacoustic spectroscopy (QEPAS) gas sensing systems, specifically targeting the detection of decomposition products in sulfur hexafluoride (SF6). Through theoretical analysis and simulations, the geometrical parameters of the T-shaped QTF were optimized to achieve a low resonant frequency of 12.46 kHz and a quality factor of 4,587 in SF6 gas matrix. The optimized system demonstrated a minimum detection limit (MDL) of 1 ppm for C2H2 in SF6 matrix, with a normalized noise equivalent absorption (NNEA) coefficient of 2.037 × 10−8 cm-1 W/√Hz. This study successfully validates the effectiveness of the T-shaped QTF for sensitive gas detection in SF6 matrix, providing a promising technical solution for online monitoring of decomposition products and fault diagnosis in SF6-insulated equipment.